China's global power: Estimating Chinese foreign direct investment in the electric power sector. (January 2020) - Li, Zhongshu; Gallagher, Kevin P.; Mauzerall, Denise L.
Abstract: We analyze the spatial and technological distribution of China's overseas electric power investments around the world, and the pollution intensity of Chinese coal fired power plants relative to those held by non-Chinese entities. We find that Chinese firms hold approximately 115 billion USD in electric power assets globally, with an average of 73% ownership stake in a total capacity of 81 GW. Chinese power investments span the globe but are largely found in developing countries, particularly in Asia and Latin America. The vast majority of Chinese investment goes to coal (24.5 GW), gas (20.5 GW) and hydropower (18.1 GW), while the share of wind (7.2 GW) and solar (3.1 GW) is relatively small but may be rising. The energy mix of Chinese overseas investment is similar to the existing world portfolio. Within the coal sector, between 2011 and 2017, the majority of Chinese greenfield investment in coal used supercritical technologies (58 percent) while only 34 percent of non-Chinese coal plants built during this period were supercritical. Highlights: A comprehensive database is compiled to record all Chinese overseas power generating projects. By 2017, China invested a total of 115 billion USD in 81 GW of power generating assets overseas. Chinese investment is largely found in emerging economies and is dominated by coal, gas and hydro power.